Pragmatic Aspects of Metalinguistic Utterances - Tonyan, Marika (Armenian Folia Anglistika, 2016)
Verbal communication is an extremely many-faceted and complex phenomenon, and should be seen as a process which, besides sending and receiving messages about the object world, can also be focused on the use of the code through which the verbal interaction is taking place. Such spheres as teaching, translation, scientific discourse, court procedures, psychological treatment, to say nothing of verbal art, are obviously metalinguistically-oriented. However, in everyday interaction as well the discussion of metalinguistic issues by the interlocutors is almost as common as a talk about extralinguistic reality. The aim of the present study is to examine the interrelation of metalinguistic and pragmatic characteristics of utterances in everyday speech. We will try to show that only if a certain utterance of metalinguistic nature is perceived as such by the speaker and hearer, can communication be pragmatically successful. Conversely, provided that the interlocutors take into account certain pragmatic factors, the utterance can be actualized and realized as a metalinguistic one, the result being the interlocutors’ mutual understanding.